2018
DOI: 10.1002/lary.27425
|View full text |Cite
|
Sign up to set email alerts
|

Initial and Long‐term Retention of Robotic Technical Skills in an Otolaryngology Residency Program

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…They found that the approach was feasible and led to appropriate improvement in clinical skills, with 85% of trainees completing a skills assessment within their allotted time. Shay et al 29 also implemented a multiphase robotic skills training course with components of robotic device docking/draping, simulator training, and dry lab exercises. This led to skill acquisition and retention at one and six month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the approach was feasible and led to appropriate improvement in clinical skills, with 85% of trainees completing a skills assessment within their allotted time. Shay et al 29 also implemented a multiphase robotic skills training course with components of robotic device docking/draping, simulator training, and dry lab exercises. This led to skill acquisition and retention at one and six month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Our group therefore set out to investigate the specific technical aspects that differentiate TORS from the other robotic‐assisted surgical specialties. Based on previous experience with resident robotic surgical training, 47 as well as experience as a established surgeon proctoring, the least intuitive aspect of TORS performance is the maneuvering within the fixed space confined by the teeth, tongue, and mandible. Uncountable episodes would see trainees (as well as established surgeons) aiming to reach a target within the pharyngolarynx by advancing the instrument in a direct vector of motion, only to be frustrated by some unseen obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…This represents a critical goal of ultimately achieving improved patient outcomes through higher skilled surgical performances, which was shown in the frequently referenced New England Journal of Medicine article by Berkmeyer and colleagues, which demonstrated precisely this relationship between surgical skill and surgical outcome. 38 A review of all English language peer-reviewed published TORS cirrulum proposals [39][40][41][42][43][44][45][46][47] along with their relative strengths and limitations, are summarized in Table I. After a thorough analysis of these proposed TORS-specific training curricula, a few patterns emerge.…”
Section: Literature Review Of Tors Training Curriculamentioning
confidence: 99%
See 1 more Smart Citation
“…6,8 These simulation-based models are known to improve safety and provide cost-savings to the health care system via a reduction in morbidity. 2,4,9,10 The aim of this study is to validate a wax-based model which can reliably differentiate experienced and inexperienced cast saw users.…”
mentioning
confidence: 99%